2017
DOI: 10.1111/jav.01070
|View full text |Cite
|
Sign up to set email alerts
|

Wintering areas predict age‐related breeding phenology in a migratory passerine bird

Abstract: Understanding connections between breeding, stopover and wintering grounds for long‐distance migratory birds can provide important insight into factors influencing demography and the strength of carry‐over effects among various periods of the annual cycle. Using previously described, multi‐isotope (δ13C, δ15N, δ2H) feather isoscapes for Africa, we identified the most probable wintering areas for house martins Delichon urbica breeding at Badajoz in southwestern Spain. We identified two most‐probable wintering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…In contrast, young birds wintering in habitats with higher rainfall had a lower probability of becoming infected compared with young birds wintering in habitats with lower rainfall. Unlike previous studies in other bird species, we were also able to associate House Martins with specific wintering areas using assignment to isoscapes , L opez-Calder on et al 2017a, where we were better able to interpret climate regimes. For instance, Great Reed Warblers wintering in tropical Africa suffer a higher haemosporidian prevalence associated with water-stressed habitats (Yohannes et al 2008).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, young birds wintering in habitats with higher rainfall had a lower probability of becoming infected compared with young birds wintering in habitats with lower rainfall. Unlike previous studies in other bird species, we were also able to associate House Martins with specific wintering areas using assignment to isoscapes , L opez-Calder on et al 2017a, where we were better able to interpret climate regimes. For instance, Great Reed Warblers wintering in tropical Africa suffer a higher haemosporidian prevalence associated with water-stressed habitats (Yohannes et al 2008).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, our results indicate that age-class is another source of variance to take into account in these kinds of studies. Unlike previous studies in other bird species, we were also able to associate House Martins with specific wintering areas using assignment to isoscapes , L opez-Calder on et al 2017a, where we were better able to interpret climate regimes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In an ecological context, carry-over effects occur when the previous history and experience of an individual explains its current performance in a given situation 1 . Many studies of migratory birds have found that environmental conditions experienced during winter have carry-over effects in terms of subsequent body condition and breeding phenology 2 7 . However, few studies have found carry-over effects of environmental conditions from winter areas on final reproductive success 8 12 .…”
Section: Introductionmentioning
confidence: 99%